Efeitos do exercício intenso e do condicionamento aeróbio associado a suplementação com cromo ou carnitina sobre a microbiota fecal de potras - Almeida, Maria Luiza Mendes de [UNESP] (2015)
Recent studies performed in humans and rats reported that exercise could alter the intestinal microbiota. Evidence indicated that this microbial community is involved in the metabolic homeostasis of the host. Moreover, studies about ergogenic substances are scarce in the literature on intestinal microbiota. This study aimed to assess the impact of acute exercise and aerobic conditioning, associated either with chromium or L-carnitine supplementation, on the intestinal microbiota of fillies. Twelve Mangalarga Marchador fillies in incipient fitness stage were distribuided into four groups: control (no exercise), exercise, L-carnitine and chromium. The fillies underwent two incremental exercise tests, before and after training on a treadmill for 42 days at 70-80% of the lactate threshold intensity. Fecal samples were obtained before and 48 hours after the acute exercise (incremental exercise test). Bacterial populations were characterized by sequencing the V4 region of the 16S rRNA gene using the MiSeq Illumina platform, and 5,224,389 sequences were obtained from 48 samples. The results showed that the three most abundant phyla were Firmicutes (50.22%), Verrucomicrobia (15.13%), followed by bacteria that were not classified at the phylum level (13.80%). The genera with the highest relative abundance were unclassified Clostridiales (17.06%), 5 genus incertae sedis (12.98%) and unclassified bacteria (12.95%). Our results indicated that intense physical activity and aerobic conditioning might change the composition and structure of the intestinal bacterial population in fillies. The intra-group comparison showed that chromium or L-carnitine caused moderate changes in the fecal microbiota of fillies. However, the results of the supplemented groups were not different from the exerciseonly group. Thus, further studies using a larger sampling are needed to further investigate these changes